1967
DOI: 10.1246/bcsj.40.511
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of trans-Diaquo-bis(pyridine-2-carboxamide)-nickel(II) Chloride, [Ni(H2O)2(piaH)2]Cl2

Abstract: The Crystal Structure of [Ni(H2O) The crystal structure of trans-diaquo-bis(pyridine-2-carboxamide)nickel(II) chloride, [Ni-(H2O)2(piaH)2]Cl2, was determined by X-ray diffraction and refined by three-dimensional leastbuilt up of centrosymmetric complex ions and chloride ions. Two ligand molecules are coordinated to the nickel atom in trans position with amide oxygen atoms and ring nitrogen atoms. (Ni-N, 2.02 A, Ni-O, 2.05 A). The ligand molecules are nearly planar and they are approximately in one plane with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
1978
1978

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In the course of studies on the bivalent metal complexes of acid amides, X-ray crystal analyses of [Ni(pia)2]2H20 (Nawata, Iwasaki & Saito, 1967), [Ni(H20)2(piaH)2]CI2 (Masuko, Nomura & Saito, 1967), [Cu(H20)2(piaH)2]Cl2 (Brown, MacSween, Mercer & Sharp, 1971) and [Cu(CIO4)2(paaH)2] (Sekizaki, Marumo, Yamasaki & Saito, 1971) have revealed that the first complex has a structure with square-planar coordination through the amide nitrogen and ring nitrogen atoms of the ligand, while the remaining three have a structure with octahedral or distorted octahedral coordination through the amide oxygen and ring nitrogen atoms where piaH and paaH denote pyridine-2-carboxamide and pyridine-2-acetamide respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of studies on the bivalent metal complexes of acid amides, X-ray crystal analyses of [Ni(pia)2]2H20 (Nawata, Iwasaki & Saito, 1967), [Ni(H20)2(piaH)2]CI2 (Masuko, Nomura & Saito, 1967), [Cu(H20)2(piaH)2]Cl2 (Brown, MacSween, Mercer & Sharp, 1971) and [Cu(CIO4)2(paaH)2] (Sekizaki, Marumo, Yamasaki & Saito, 1971) have revealed that the first complex has a structure with square-planar coordination through the amide nitrogen and ring nitrogen atoms of the ligand, while the remaining three have a structure with octahedral or distorted octahedral coordination through the amide oxygen and ring nitrogen atoms where piaH and paaH denote pyridine-2-carboxamide and pyridine-2-acetamide respectively.…”
Section: Introductionmentioning
confidence: 99%